Increased Prevalence of Symptomatic Human Intestinal Spirochetosis in MSM with High-Risk Sexual Behavior in a Cohort of 165 Individuals - Ramón Pérez-Tanoira; Marta del Palacio Tamarit; Ana María Vicente Montaña; David Carmena; Pamela Köster; Miguel Górgolas; José R. Fortes Alen; Alfonso Cabello-Úbeda; Laura Prieto-Pérez (Tropical Medicine and Infectious Disease, 2023)
Human intestinal spirochetosis (HIS) can cause gastrointestinal symptoms, although asymptomatic infections have been described. Individuals from low-income countries, people living with HIV, and men who have sex with men (MSM) show increased risk. A retrospective review of all patients diagnosed with HIS (n = 165) between January 2013 and October 2020 at a tertiary hospital in Madrid, Spain, was performed to assess risk factors for symptomatic HIS, symptoms, and response to treatment. Most patients were male (n = 156; 94.5%), 86.7% were MSM, and 23.5% practiced chemsex, of whom most were symptomatic (p = 0.039). Most patients (78.4%) reported unprotected oral-anal intercourse. A total of 124 (81.1%) were symptomatic; diarrhea was the most common complaint (68.3%). Multivariable regression showed increased odds of symptoms associated with age under 41 (odds ratio 5.44, 95% CI 1.87–15.88; p = 0.002). Colonoscopy was normal in 153 (92.7%). Furthermore, 66.7% presented previous or concomitant sexually transmitted diseases (STDs). Among the patients, 102 underwent testing for other gastrointestinal pathogens, with positive results in 20 (19.6%). All symptomatic patients without concomitant gastrointestinal infection presenting improvement on follow-up (42 of 53) had received either metronidazole or doxycycline (p = 0.049). HIS should be considered as a cause of chronic diarrhea in MSM with high-risk sexual behavior after other causes have been ruled out; treatment with metronidazole is recommended. Coinfection with other STDs is common.